Мошенничество при продаже недвижимости в природоохранных зонах - Iakubina E. V. (Priority directions of scienceand education development, 2017)
The author has considered topical issues of fraud in the sale of real estate in environmental zones.
Keywords: право; Россия; недвижимость; Russia; law; Real estate